Assessment of reactive-control compression ignition engine performance and emissions using spirulina microalgae biodiesel in conjunction with methanol as low-reactive fuel - Munimathan, Arunkumar; Rajendran, Silambarasan; Agbulut, Umit (SPRINGER, 2024)
Due to their numerous uses and great fuel economy, diesel engines have been around for millennia. Despite these benefits, diesel engines have been found to pollute the environment severely. Most of the problems were caused by these engines' combustion processes, engine loads, and exhaust particles. The RCCI engine used in the experiment has 20% lower fuel and 80% high reactive fuel. In this research, methanol, and algae biodiesel blends with dimethyl ether acted as lower and higher reactive fuels, respectively, and these fuels were used to analyze the performance and emission in the RCCI engine. Among the 80% of high reactive fuel, blends contain different proportions of algae biodiesel and diethyl ether such as 32B, 28B4ME, 24B8ME, 20B12ME, and 16B16ME. A single-cylinder, four-stroke RCCI engine with a speed of 1500 rpm is used for the experiment. In the tests, the brake power is varied from 1 to 5 kW with an interval of 1 kW. In the results, BTE, BSFC, and EGT engine performance as well as NOX, HC, CO2, and smoke emissions. According to the experimental findings, the fuel properties of 16B16ME show a calorific value of 34.7 /MJ kg-1 and BTE shows improvement for all additive added fuel and 16B16ME shows higher BTE of 32.5% than other fuel blends, Similarly NOx emission also reduced for 628 ppm for 16B16ME than other fuel blends. Therefore 16B16ME is a suitable blend than other blends in RCCI engine based on the experimental results achieved in the present research.
Keywords: Microalgae; Biodiesel; Engine efficiency; Tailpipe emission; Alcohol; Transesterification; Thermodynamics; Chemistry